2013
DOI: 10.1016/j.jaad.2012.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Fitzpatrick skin phototype is an independent predictor of squamous cell carcinoma risk after solid organ transplantation

Abstract: Background Solid organ transplant recipients are at an increased risk of developing squamous cell carcinoma of the skin after transplant. In predominantly Caucasian cohorts, Fitzpatrick skin type (FST) has been reported to be a risk factor for developing post-transplant skin cancers. Objective Our goal was to determine if Fitzpatrick skin type is a statistically significant risk factor for the development of squamous cell carcinomas after solid organ transplant in a diverse US population of transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 29 publications
6
67
1
Order By: Relevance
“…In particular, there is a dramatic increase in the incidence of aggressive SCC. TSCC lesions are furthermore associated with greatly elevated rates of metastases and recurrence, leading to a 3-year mortality, which can reach as high as 46% (7,24,25). In the present study, we focused on CSA, a mainstay of immunosup-pressive therapy in OTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there is a dramatic increase in the incidence of aggressive SCC. TSCC lesions are furthermore associated with greatly elevated rates of metastases and recurrence, leading to a 3-year mortality, which can reach as high as 46% (7,24,25). In the present study, we focused on CSA, a mainstay of immunosup-pressive therapy in OTR.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings demonstrated that both IL-22 and CSA increased SCC cell proliferation and invasion in vitro. It has been shown that TSCC lesions are associated with greatly elevated rates of metastases and recurrence, leading to a 3-year mortality, which can reach as high as 46% (7,24,25). CSA treatment of OTR may be driving SCC proliferation, migration, and invasion via the IL-22 axis.…”
Section: Discussionmentioning
confidence: 99%
“…[89][90][91] Most SCCs arise on sun-exposed sites and other risk factors include tobacco smoking, fair phenotype, sun exposure, and correlates of high cumulative sun exposure such as pre-transplant actinic damage or SCC, male gender and older age. 92,93 Multiple SCCs frequently develop in transplant recipients and tumor behavior is more aggressive than in immune competent individuals. 94 The relative risk of cutaneous BCC in transplant recipients is around 16-fold.…”
Section: People With Hivmentioning
confidence: 99%
“…All rights reserved. transplant include older age at transplantation, fair skin type, high sun exposure, frequent sunburns in childhood, a history of skin cancer pre-transplantation and rejection episodes in the first year of transplantation (47, 57,58). Therefore, the avoidance of azathioprine in OTRs with one or more of these risk factors may help reduce the future risk of SCC.…”
Section: Accepted Articlementioning
confidence: 99%